Democracy's defenders : U.S. Embassy Prague, the fall of communism in Czechoslovakia, and its aftermath - Eisen, Norman L., 1961- (Brookings Institution Press, 2020)
"Democracy's Defenders offers a behind-the-scenes account of the little-known role played by the U.S. embassy in Prague in the collapse of communism in what was then Czechoslovakia. Featuring fifty-two newly declassified diplomatic cables, the book shows how the staff of the embassy led by U.S. Ambassador Shirley Temple Black worked with dissident groups and negotiated with the communist government during a key period of the Velvet Revolution that freed Czechoslovakia from Soviet rule. In the vivid reporting of these cables, Black and other members of the U.S. diplomatic corps in Prague describe student demonstrations and their meetings with anti-government activists. The embassy also worked to forestall a violent crackdown by the communist regime during its final months in power. Edited by Norman L. Eisen, who served as U.S. Ambassador to the Czech Republic from 2011 to 2014, Democracy's Defenders contributes fresh evidence to the literature on U.S. diplomatic history, the cold war era, and American promotion of democracy overseas. In an introductory essay, Eisen places the diplomatic cables in context and analyzes their main themes. In an afterword, Eisen, Czech historian Dr. Mikuláš Pešta, and Brookings researcher Kelsey Landau explain how the seeds of democracy that the United States helped plant have grown in the decades since the Velvet Revolution. The authors trace a line from U.S. efforts to promote democracy and economic liberalization after the Velvet Revolution to the contemporary situations of what are now the separate nations of the Czech Republic and Slovakia"--